Aplicación de una herramienta digital para la gestión de documentación por entidades ofertantes en una institución prestadora de servicios de salud (2024)
This project arises from the need to create a tool that facilitates the document collection processes through a digital application, taking into account different factors such as easy interactivity, alignment with institutional colors, and information storage.